2021
DOI: 10.3390/ijms222212330
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Have to Know about PD-L1 Expression in Prostate Cancer? A Systematic Literature Review. Part 3: PD-L1, Intracellular Signaling Pathways and Tumor Microenvironment

Abstract: The tumor microenvironment (TME) includes immune (T, B, NK, dendritic), stromal, mesenchymal, endothelial, adipocytic cells, extracellular matrix, and cytokines/chemokines/soluble factors regulating various intracellular signaling pathways (ISP) in tumor cells. TME influences the survival/progression of prostate cancer (PC), enabling tumor cell immune-evasion also through the activation of the PD-1/PD-L1 axis. We have performed a systematic literature review according to the PRISMA guidelines, to investigate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 262 publications
0
13
0
Order By: Relevance
“…Several studies have indicated that intracellular Wnt/β‐catenin, JAK/STAT, ERK/MEK, Akt–mTOR and NF‐kB signalling pathways are involved in PD‐L1 upregulation in prostate cancer 28 . RNF43 has been demonstrated to act as an inhibitor of Wnt signalling by selectively ubiquitinating frizzled receptor, and STAT1 activation and PD‐L1 expression were increased in RNF43‐deficient mice 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have indicated that intracellular Wnt/β‐catenin, JAK/STAT, ERK/MEK, Akt–mTOR and NF‐kB signalling pathways are involved in PD‐L1 upregulation in prostate cancer 28 . RNF43 has been demonstrated to act as an inhibitor of Wnt signalling by selectively ubiquitinating frizzled receptor, and STAT1 activation and PD‐L1 expression were increased in RNF43‐deficient mice 29,30 .…”
Section: Resultsmentioning
confidence: 99%
“…To better present the data of our SLR, we have split the discussion of our results into different articles, highlighting relevant subtopics: PD-L1 IHC expression in PC with discussion of pre-analytical and interpretation variables; correlations of PD-L1 expression with clinic–pathological features in PC patients; PD-L1 intracellular signaling pathways in PC cells and regulation of the tumor microenvironment; pre-clinical models (cell lines, mouse models) and experimental treatments affecting PD-L1 expression in PC cells; genetic and epigenetic regulation of PD-L1; PD-L1 expression in liquid biopsies, etc. [ 260 , 261 , 262 , 263 , 264 , 265 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result of functional enrichment analysis at both bulk RNA-seq level and single-cell level indicated the presence of differences in the tumor immune microenvironment between the two Classes, such as cytokine pathway, humoral immune response and IL-17 signaling pathway. Programmed cell death ligand 1 (PD-L1) inhibitors kill tumor cells by triggering pyroptosis ( 65 ), while IL-17 promotes PD-L1 expression in tumor cells by PD-1+ immune cell intratumor infiltration ( 66 ), suggesting that IL-17 may be a potential target for enhancing the performance of PD-L1 inhibitors by increasing pyroptosis of tumor cells. We observed a higher infiltration of macrophages in Class1, while it has been reported that macrophages can release reactive oxygen species (ROS) and thus trigger pyroptosis ( 67 ).…”
Section: Discussionmentioning
confidence: 99%